Droplet spectrum and fungicide efficiency in the control of Asian soybean rust (Phakopsora pachyrhizi Syd. and P. Syd.) (2018)
The aim of this study was to evaluate the chemical control of Asian soybean rust (Phakopsora pachyrhizi Syd. and P. Syd.) using different tips and spray nozzles under controlled conditions. Rooted trifolia placed inside an acrylic box containing macronutrients, micronutrients and vitamins were treated with epoxiconazol + pyraclostrobin, ciproconazol + azoxystrobin and tebuconazol fungicides. These fungicides were sprayed at a height of 0.5 m with two knapsack sprayers pressurized with CO2 gas (drop generator in four spray tips spaced by 0.5 m from each other) and another rotating nozzle (drop generator through a rotating nozzle). Untreated trifolia were controls. Water sensitive paper was placed next to each acrylic box to obtain median volume diameter (MVD), number of droplets.cm-2 and coverage (%). Trifolia were inoculated 24 hours after that these were treated with fungicide, using a spore concentration adjusted to 2 x 104 uredospores.mL-1. Then, the number of lesions and uredia.cm-2 in central leaflets were quantified. Lower number of lesions and uredia.cm-2 were observed in leaflets treated with two fungicide mixtures using an AIRMIX 11001 tip. A lower VMD was found in leaflets sprayed with the fungicides azoxystrobin + epoxiconazol and tebuconazol, when compared to the leaflets treated with another mixture. The Asian rust control, as well as the number of droplets.cm-2 and coverage, seems to be dependent on the interactions among fungicides and tips or nozzles.